2014
DOI: 10.3390/toxics2020092
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Health Risk in Human Populations Due to Chlorpyrifos

Abstract: A wide ranging survey was carried out of the available data from ten different countries on human exposure to chlorpyrifos, in many different occupational and nonoccupational settings. Low levels of chlorpyrifos residues were found to be widely distributed in the global human population, but most of these do not constitute a public health risk, as evaluated using the U.S. Environmental Protection Agency (USEPA) Guidelines. For example, the general populations in USA, Germany and Italy had detectable residue le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…However, HQ values (HQ>1) according to the chronic guideline value (0.3 μg/kg/day) of the USEPA were obtained 1.3076, indicating that 5% of the target population are at risk of chronic health effects. In agreement, Marasinghe et al also showed that only a subgroup of pregnant mothers may pose the health risk of chlorpyrifos exposure [ 20 ]. Likewise, Atabila et al, also assessed the health risk of exposure to chlorpyrifos among applicators on rice farms in Ghana and showed that the median exposed and the 5% highly exposed groups are at high risk of acute adverse health effects due to the exposure to chlorpyrifos.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…However, HQ values (HQ>1) according to the chronic guideline value (0.3 μg/kg/day) of the USEPA were obtained 1.3076, indicating that 5% of the target population are at risk of chronic health effects. In agreement, Marasinghe et al also showed that only a subgroup of pregnant mothers may pose the health risk of chlorpyrifos exposure [ 20 ]. Likewise, Atabila et al, also assessed the health risk of exposure to chlorpyrifos among applicators on rice farms in Ghana and showed that the median exposed and the 5% highly exposed groups are at high risk of acute adverse health effects due to the exposure to chlorpyrifos.…”
Section: Resultssupporting
confidence: 55%
“…The primary metabolite of CFP is the TCP and its urinary levels have been assumed to mirror the current exposure to CPF. Hence, biomonitoring studies have measured urinary TCP concentration as a biomarker to evaluate exposure to CPF [ 20 , 24 , 25 ]. Jaacks et al, have detected TCP in urine samples of nearly all studied pregnant women with geometric mean (95% CI) values of 3.17 (2.82–3.56) μg/g of creatinine [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study also confirm that continuous exposure to chemical formulations of CPF are a major concern for human health. In Sri Lanka, the occupational exposure to CPF of the farmers ranged from 2500 to 90,000 ng/kg/day [76]. Therefore, the long-term exposure to chemical formulation of CPF should raise a concern.…”
Section: Discussionmentioning
confidence: 99%
“…The technique, however, cannot usually account for the variability of exposure and sensitivity among a population. A strategy to partly address this weakness is to calculate HQ at various percentiles of exposure (Cao et al, 2010;Phung et al, 2012;Marasinghe et al, 2014;Edokpolo et al, 2015;Sadler et al, 2016). In this study, HQ was calculated for exposures at CP 50 (HQ 50 ) and CP 95 (HQ 95 ), which represents the risk among the median-exposed group and the 5% highly-exposed group, respectively.…”
Section: The Hazard Quotient Techniquementioning
confidence: 99%